Biology of Tortoiseshell Beetle (Aspidomorpha miliaris Fabr.) on Sweetpotato (Ipomoea batatas Lam) and Its Relatives as Affected by Hosts’ Nutritional Profile - Vasquez, Erlinda A.; Asio, Luz G.; Ferraren, Dilberto O.; Dacera, Resa M. (Annals of Tropical Research, 2021)
Several insect pests attack the foliage of sweetpotato at different stages of crop growth which contribute to yield reduction. Weeds belonging to the same genera as the main host can act as alternate hosts of insect pests. The study evaluated the biology of tortoiseshell beetle in the laboratory at an ambient temperature of 27-30oC and 85-90% RH on sweetpotato (Ipomoea batatas) as main host and four other Ipomoea species: three-lobe morning glory (I. triloba), beach morning glory (Ipes-caprae), swamp morning glory (I. aquatica), and five-finger morning glory (I. pentaphylla Syn. I. cairica) as alternate hosts. The beetle underwent four developmental stages – egg, larva, pupa, and adult. It completed its development within 4-6 weeks from egg-laying to adult emergence of 26-40 days, an average of 27.55 to 39.01 days. The total development period of male and female A. miliaris on I. batatas, I. triloba, I. pes-caprae, I. aquatica, and I. pentaphylla were 27.55 and 30.72, 27.52 and 30.49, 29.94 and 35.06, 33.25 and 38.11, and 33.70 and 39.01 days, respectively. Adult longevity of males and females was longer on I. batatas and I. triloba, followed by I. aquatica), I. pentaphylla, and lastly, I. pes-caprae. The highest number of eggs laid was recorded in I. batatas (202.7), followed by I. triloba (173.2), I. pes-caprae (76.0), I. aquatica (71.7), and I. pentaphylla (59.7). The highest egg viability of more than 90% was recorded in I. batatas and I. triloba. Mortality occurred towards the later part of larval development, with the lowest mortality of 8.33% in I. batatas. The host plants ‘ high protein, N, P, and K contents influenced the shorter life cycle, higher reproductive rate, high percentage egg hatchability, lower mortality, and longer life span. Increased mortality and abnormal wet frass in I. pes-caprae could be accounted for by exceptionally high sugar content in the leaves and secondary metabolites present, especially in other host plants that may have insecticidal activity. Since A. miliaris was also able to complete its life cycle and reproduce on the four weed species, the insect continues to survive without sweetpotato. Any management strategy for this insect by destroying the Ipomoea weed hosts eliminates other sources of infestation in the field.